2018
DOI: 10.3389/feart.2018.00060
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Study to Evaluate Debris Flow Hazard in Alpine Environment

Abstract: Debris flows are among the most dangerous natural processes affecting the alpine environment due to their magnitude (volume of transported material) and the long runout. The presence of structures and infrastructures on alluvial fans can lead to severe problems in terms of interactions between debris flows and human activities. Risk mitigation in these areas requires identifying the magnitude, triggers, and propagation of debris flows. Here, we propose an integrated methodology to characterize these phenomena.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…The analysis of the pre-event morphology between '50s and nowadays also showed that slopes on the right side of Ru Secco Creek were routed by debris flows before their transformation in a ski resorting area while the left side was not subjected to debris flow phenomena (Figures S4, S5). In the present case study, the environmental changes due to man works can stop or reduce debris flow activity in areas prone to debris flow susceptibility, while those due to natural causes, as the formation of debris deposits caused by local terrain instabilities, if connected to the channel network (Cavalli et al, 2013;Tiranti et al, 2016Tiranti et al, , 2018, allow the conditions for debris flow occurrence, where it never did. Both the historical basins where debris flows formed until '50s and the new one of Ru Salvela are debris flow dominated according to the geomorphic indexes: the ruggedness number of Melton close or larger than 1 [0.75 is the inferior threshold value according to DeScally and Owens (2004)] and local slope larger than 0.6 m/m in the schematic diagram between local slope and drainage area proposed by Montgomery and Foufoula-Georgiou (1993) for the hillslope to valley transition also used by Tarolli and Dalla Fontana (2009).…”
Section: Discussion Of Resultsmentioning
confidence: 91%
“…The analysis of the pre-event morphology between '50s and nowadays also showed that slopes on the right side of Ru Secco Creek were routed by debris flows before their transformation in a ski resorting area while the left side was not subjected to debris flow phenomena (Figures S4, S5). In the present case study, the environmental changes due to man works can stop or reduce debris flow activity in areas prone to debris flow susceptibility, while those due to natural causes, as the formation of debris deposits caused by local terrain instabilities, if connected to the channel network (Cavalli et al, 2013;Tiranti et al, 2016Tiranti et al, , 2018, allow the conditions for debris flow occurrence, where it never did. Both the historical basins where debris flows formed until '50s and the new one of Ru Salvela are debris flow dominated according to the geomorphic indexes: the ruggedness number of Melton close or larger than 1 [0.75 is the inferior threshold value according to DeScally and Owens (2004)] and local slope larger than 0.6 m/m in the schematic diagram between local slope and drainage area proposed by Montgomery and Foufoula-Georgiou (1993) for the hillslope to valley transition also used by Tarolli and Dalla Fontana (2009).…”
Section: Discussion Of Resultsmentioning
confidence: 91%
“…However, important limitations characterizing these methods can be pointed out and render them unsuitable for our research objectives. For instance, several authors have replicated the methodology developed by Cavalli et al (2013) and highlighted the indispensability of coupling such automatic approaches with geomorphological analysis based on aerial images and in situ field surveys, as relatively frequent discrepancies between computed connectivity index values and field observations were detected (e.g., Messenzehl et al, 2014;Micheletti and Lane, 2016;Tiranti et al, 2018). In addition, these different approaches for automatically inferring connectivity are generally developed at the catchment scale and aim at representing the spatial variability in sediment connectivity.…”
Section: Subjectivity Of the Approachmentioning
confidence: 99%
“…For example, in terms of the slope index, because of the lack of a unified standard for the slope threshold, different scholars have reached very different results when determining the ranges of a slope, resulting in uncertainty in the assessment results. There are numerous risk assessment indices for geo-hazards, including hazard-forming environments, hazard factors, and hazard-bearing bodies [8]- [10].…”
Section: Introductionmentioning
confidence: 99%